2016
DOI: 10.1016/j.marenvres.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of ammonia oxidizers in the sediments of the Gulf of Finland, Baltic Sea

Abstract: The diversity and dynamics of ammonia-oxidizing bacteria (AOB) and archaea (AOA) nitrifying communities in the sediments of the eutrophic Gulf of Finland (GoF) were investigated. Using clone libraries of ammonia monooxygenase (amoA) gene fragments and terminal restriction fragment length polymorphism (TRFLP), we found a low richness of both AOB and AOA. The AOB amoA phylogeny matched that of AOB 16S ribosomal genes from the same samples. AOA communities were characterized by strong spatial variation while AOB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Importantly from the environmental point of view, avoiding NH 3 losses can lead to maintaining nutrients in the manure/slurry and therefore applying more nutrients to the soil when spreading manure or slurry, thus requiring fewer mineral fertilizers and bringing benefits to the environmental sustainability, plus valorizing an already available resource that is free of charge. Finally, while high NH 3 concentration in air may represent a local issue, damages to ecosystems from NH 3 are not only local and are widely investigated due to the main effects of acidification and eutrophication on biodiversity loss in coastal and estuarial areas, such as in the study by Vetterli et al (2016) .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly from the environmental point of view, avoiding NH 3 losses can lead to maintaining nutrients in the manure/slurry and therefore applying more nutrients to the soil when spreading manure or slurry, thus requiring fewer mineral fertilizers and bringing benefits to the environmental sustainability, plus valorizing an already available resource that is free of charge. Finally, while high NH 3 concentration in air may represent a local issue, damages to ecosystems from NH 3 are not only local and are widely investigated due to the main effects of acidification and eutrophication on biodiversity loss in coastal and estuarial areas, such as in the study by Vetterli et al (2016) .…”
Section: Discussionmentioning
confidence: 99%
“…Öre River), whereas Nitrosospira ‐like OTUs were confined to the rivers, indicating a preference for freshwater. Both genera have, however, previously been found in Baltic Sea waters and sediments (Kim et al ., ; Vetterli et al ., ), and in sediments (Chang et al ., ) and waters (Bano and Hollibaugh, ; O'Mullan and Ward, ; Kim et al ., ) from multiple localities. It is not understood what governs the distribution of the two genera, possibly as a consequence of difficulties associated with correlating single environmental factors to complex combinations of variables shaping AOB diversity in dynamic environments (Francis et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors have been widely confirmed to affect microbial distributions in estuarine ecosystems 14 , 22 , 26 , 31 . In the present study, both the Mantel test and RDA indicated carbon contents appeared to be the key explanatory variables influencing the sediment AOM community structures.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance and diversity of AOA and AOB can also be influenced by the variation of environmental factors. Many studies demonstrated a wide range of abiotic factors shaping the AOM distribution patterns, such as pH 14 , 21 , salinity 22 , 23 , ammonium (NH 4 + -N) and organic matter 16 , 24 , 25 , as well as spatial and temporal factors 26 . As the substrate of ammonia oxidation, ammonia has been considered as a primary factor to manipulate AOMs’ distribution.…”
Section: Introductionmentioning
confidence: 99%